Karakteristik Batugamping Dan Porositas Terhadap Potensi Reservoir Air Tanah Di Desa Buhudaa, Kabupaten Gorontalo - Sino, Widya Indriani H.; Zainuri, Ahmad; Akase, Noviar (Universitas Negeri Gorontalo, 2025)
Reservoir rocks are characterized by their ability to allow water to infiltrate beneath the surface, enabling them to store and transmit fluids due to their permeability. Porosity refers to the presence of pores or void spaces within rocks, which determines their capacity to store fluids. Therefore, the porosity of a rock plays a significant role in the volume of liquid or gas it can contain. The study area is located within the Ql Formation, and no prior research has been conducted on limestone reservoir rocks in Buhudaa Village, Batudaa Pantai Subdistrict, Gorontalo Regency. The research covers an area of approximately 3.3 km², including the villages of Buhudaa, Bongo, and Lopo. This study aims to map the geological conditions of the Buhudaa area and analyze the lithological characteristics and quality of limestone as a groundwater reservoir. The methods employed include petrographic analysis and specific gravity testing. The results indicate that the geomorphological conditions of the area consist of structural and low-structural hills. The limestone was classified into three lithofacies: Mudstone, Wackestone, and Packstone. Geological structures were identified using linear lineament analysis, which distinguished ridges and valleys. The dominant orientation of these features trends northeast–southwest. Based on Koesoemadinata’s (1980) classification, the quality of limestone as a reservoir rock in the study area ranges from fair to very good.